Body mass index and acute coronary syndromes: Paradox or confusion?. Issue 2 (April 2015) - Ariza-Solé, Albert; Salazar-Mendiguchía, Joel; Lorente, Victòria; Sánchez-Salado, José Carlos; Ferreiro, José Luis; Romaguera, Rafael; Ñato, Marcos; Gomez-Hospital, Joan Antoni; Cequier, Ángel
Background: A better prognosis in obese patients has been described in acute coronary syndromes (ACS). However, this evidence is mostly based on retrospective studies and has provided conflicting results. No study reported cause-specific mortality according to body mass index (BMI) in ACS. We aimed to prospectively assess the impact of BMI on mortality and its specific causes in ACS patients. Methods: We included non-selected ACS patients admitted in a tertiary care coronary unit, collecting baseline characteristics, management and clinical course. Patients were stratified into five clinically meaningful BMI subgroups of <20, 20–24.9, 25–29.9, 30–35, >35 kg/m 2 . The primary outcome was 1 year mortality, its causes and its association with BMI. This association was assessed by the Cox regression method. Results: We included 2040 patients in our study with a mean age of 62.1 years. Low weight patients (BMI <20) were older, with less cardiovascular risk factors, higher prevalence of chronic obstructive pulmonary disease and worse renal function. Mean follow up was 334 days. The unadjusted analysis showed lower all-cause mortality in all subgroups as compared to low weight patients. After adjusting for potential confounders, this association remained significant for patients with a BMI 20–24.9. Cardiac mortality was similar across BMI subgroups. In contrast, the adjusted analysis showed a significantly lower non-cardiac mortality in patients with a BMI 20–24.9, 25–29.9 and 30–35 as compared to low weight patients. Conclusions: Baseline characteristics in ACS patients significantly differ according to their BMI status. The prognostic impact of BMI seems mostly related to extra-cardiac causes in low weight patients.